A General Copper‐Mediated Nucleophilic 18F Fluorination of Arenes1. Issue 30 (10th June 2014) - Tredwell, Matthew; Preshlock, Sean M.; Taylor, Nicholas J.; Gruber, Stefan; Huiban, Mickael; Passchier, Jan; Mercier, Joël; Génicot, Christophe; Gouverneur, Véronique
Abstract Molecules labeled with fluorine‐18 are used as radiotracers for positron emission tomography. An important challenge is the labeling of arenes not amenable to aromatic nucleophilic substitution (SNAr) with [18F]F−. In the ideal case, the 18F fluorination of these substrates would be performed through reaction of [18F]KF with shelf‐stable readily available precursors using a broadly applicable method suitable for automation. Herein, we describe the realization of these requirements with the production of 18F arenes from pinacol‐derived aryl boronic esters (arylBPin) upon treatment with [18F]KF/K222 and [Cu(OTf)2(py)4] (OTf=trifluoromethanesulfonate, py=pyridine). This method tolerates electron‐poor and electron‐rich arenes and various functional groups, and allows access to 6‐[18F]fluoro‐L‐DOPA, 6‐[18F]fluoro‐m‐tyrosine, and the translocator protein (TSPO) PET ligand [18F]DAA1106.